2020
DOI: 10.1021/acs.inorgchem.0c00188
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Fullerene–Polyoxometalate Hybrid Exhibiting Enhanced Photocurrent Response

Abstract: A new C60-polyoxometalate compound was synthesized by a C60 derivative with a {SiW11Mn} cluster connecting through a coordination bond and characterized. The photocurrent response test showed great improvement of this new compound compared to C60 and the polyoxometalate precursor, which could be used as a potential photoelectric material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…As shown in Figure 5A, both catalysts have increased photocurrent density during the initial on/off light time, and both have different degree of decrease with increasing the response time, which may be related to the rapid photogenerated electron−hole recombination during the light exposure. 49 Even so, the photocurrent density of TCPP/Cu 2 Co 1 is significantly higher than that of Cu 2 Co 1 , indicating TCPP/Cu 2 Co 1 has a stronger interfacial charge transfer ability. From the PEIS (Figure 5B), we can see that the charge transfer resistance of TCPP/Cu 2 Co 1 is smaller than that of Cu 2 Co 1 under both light and dark conditions.…”
Section: Mor Performance Of Tcpp/cu 2 Comentioning
confidence: 93%
“…As shown in Figure 5A, both catalysts have increased photocurrent density during the initial on/off light time, and both have different degree of decrease with increasing the response time, which may be related to the rapid photogenerated electron−hole recombination during the light exposure. 49 Even so, the photocurrent density of TCPP/Cu 2 Co 1 is significantly higher than that of Cu 2 Co 1 , indicating TCPP/Cu 2 Co 1 has a stronger interfacial charge transfer ability. From the PEIS (Figure 5B), we can see that the charge transfer resistance of TCPP/Cu 2 Co 1 is smaller than that of Cu 2 Co 1 under both light and dark conditions.…”
Section: Mor Performance Of Tcpp/cu 2 Comentioning
confidence: 93%
“…The influence of assembly structure, substituents in quinolinium ring and the acidity of reaction system on the synergistic catalytic effect was studied. Fullerenes ) by coordination linkage of C60 derivative with a {SiW11Mn} cluster [72] . The results showed that the connection of SiW11Mn and C60 at molecular level can effectively improve the photoelectron conversion efficiency of materials.…”
Section: Photocatalysismentioning
confidence: 99%
“…10,11 Inorganic POMs can be covalently modified with functional organic moieties to generate POM-based organic-inorganic hybrids, which therefore enrich the diversity of POM structures and expand their application area. The POM hybrids not only introduce the advantages of organic groups (high compatibility in organic media, good processability, and diverse optical and electronic properties), [12][13][14] but also exert unexpected synergistic effects for strengthening molecular stability 15 and improving photochromic, 10 electronic storage, 16 and catalytic properties. 17 Therefore, covalent functionalization of POMs has become one of the most important research directions in POM chemistry.…”
Section: Introductionmentioning
confidence: 99%